Kasabach-Merritt Syndrome: a case study of successful treatment with vincristine and propranolol - Mazhar, Aqsa; Ghouse, Afza Naureen; Shahid, Saba; Lubna Samad (Journal of the Pakistan Medical Association, 2023)
Kasabach-Merritt syndrome is a rare condition, characterised by the presence of an enlarging vascular tumour associated with thrombocytopenia, microangiopathic haemolytic anaemia and consumptive coagulopathy. The syndrome manifests in infancy, with high morbidity and mortality rates. No standard guidelines have been established for the treatment of Kasabach-Merritt syndrome to date. To existing literature we add this report of a four-month-old female child with Kasabach-Merritt syndrome who was successfully treated with propranolol and vincristine. This drug combination helped reverse the severe thrombocytopenia as well as decrease in size of her haemangioma. Management of Kasabach-Merritt syndrome continues to be a challenge, with varying response to first line drugs. Early diagnosis and initiation of treatment in a closely monitored setting is essential to ensure good outcomes. Since this is a relatively rare condition and large studies are not feasible, documenting treatment experience for single cases or small series becomes even more important.